Innovative Delegation Application in Thai National Digital Identity Platform - Arunwatanamongkol, Pensri; Nupairoj, Natawut; Tanlamai, Uthai (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The national digital identity platform is a robust scheme that enables individuals and entities to prove who they are to digitally access critical information or services. However, current digital identity systems do not sufficiently consider delegation between entities from the viewpoint of dynamic authorizers and permissions. This study aims to understand the pain points and expectations of end-users and service providers in the Thai national digital identity platform, to design a dynamic delegation model and develop an innovative delegation application to test user acceptance. The research utilizes semi-structured interviews with 3 digital identity experts, two focus groups, one with 6 service providers, and the other one with 6 end-users. Based on results from the data analysis and conceptual prototype design, validated by experts, the proposed prototype is practical and suitable for developing a digital delegation mobile web application that is convenient, safe, secure, and reliable utilizing blockchain technology under the Thai national digital identity platform. The technology acceptance model was used to test the application acceptance with 42 participants. The result reveals that both person and businesses intend to adopt the digital delegation mobile web application. Use cases of the application include users give their power to trusted entities and Government Agency to provide services to the citizens via the authorized delegatee.